Маркетинговые системы принятия решений для увеличения результативности интернет-маркетинга - Korobkov S. A. (Новое слово в науке: перспективы развития, 2016)
Internet advertising systems and internet statistics data usage in MIS (Marketing Information Systems) and MDSS (Marketing Decision Support System)
Keywords: системы принятия решений; интернет-маркетинг; маркетинговые информационные системы; MDSS; Marketing Information Systems; Marketing Decision Support System; Internet marketing